WUJUD KODE PILIHAN BAHASA DALAM JUAL BELI DI PASAR TRADISIONAL KECAMATAN WINONG, KABUPATEN PATI - Agus Sudono (Pusbindiklat - LIPI, 2014)
The research is aimed to describe the language choice codes of purchasing in traditional market in Winong District, Pati Regency. This research uses the sociolinguistics approach. The data of this research are utterances of the sellers and the buyers in the traditional market. The sources of the data are the sellers and the buyers in the traditional market. The data were collected by using the methods of observation and interview. The data were analyzed by using contextual approach. The results of the research are as follows: (1) The codes of the language consist of Javanese and Indonesian languages; (2) The codes of speech level consist of ngoko, madya, and krama; (3) The codes of style consist of elaborated code and restricted code; (4) The codes of dialect consist of Pati dialect Javanese and standard Javanese.